Primary Care Team Perspectives on the Suitability of Telehealth Modality (Phone vs Video) at the Veterans Health Administration - Shay Cannedy; Lucinda Leung; Tamar Wyte-Lake; Michelle D. Balut; Aram Dobalian; Leonie Heyworth; Neil M. Paige; Claudia Der-Martirosian (SAGE Publishing, 2023)
Introduction: Telehealth has the potential to improve access and timeliness of care, enabling primary care teams to deliver hybrid (virtual/in-person) services that will likely extend beyond the COVID-19 pandemic. To optimize its use and sustainability, it is imperative to understand how primary care teams perceive the suitability of telehealth services, including appropriate choice of mode (telephone or video). However, there is limited research on providers' decision-making processes surrounding telehealth use in primary care, including whether to use telephone or video, which this VA-focused study addresses. We examined how primary care (PC) team members determine whether to use telehealth and the mode of delivery, in the care of patients. Methods: Qualitative case study that included 15 semi-structured interviews with employees who provided or supported telehealth care at primary care clinics at the Veterans Health Administration. We used a team-based rapid analysis approach to identify experiences using telehealth soon after COVID-19's emergence, consisting of the creation of structured summaries of each transcribed interview. The lead author then identified and compiled themes and sub-themes related to the suitability of telehealth in primary care, as well as associated quotes from transcripts. Resulting themes and quotes were reviewed and validated by 2 members of the project team. Results: Primary care team members considered several factors when assessing both the suitability of telehealth for appointments, and mode of use. They were largely guided by patient-related factors including patient preferences, specific health issues, and access to technology. Additional considerations centered on team members' personal preferences and factors that supported the wellbeing of the team, such as the flexibility to work from home (work-life balance) and protection from infection. Generally, participants viewed the option of both telephone and video telehealth modalities as useful tools in the care of patients although a few respondents emphasized its inferiority to in-person care. Conclusions: Determining the suitability of telehealth services, including appropriate choice of mode is complex. Its suitability is tied to a variety of factors related to multilevel resources, preferences, and timing. When appropriate, telehealth should be considered a useful tool in the care of patients and for employee well-being.